2017
DOI: 10.1007/s13280-016-0894-2
|View full text |Cite
|
Sign up to set email alerts
|

Sea ice and primary production proxies in surface sediments from a High Arctic Greenland fjord: Spatial distribution and implications for palaeoenvironmental studies

Abstract: In order to establish a baseline for proxy-based reconstructions for the Young Sound–Tyrolerfjord system (Northeast Greenland), we analysed the spatial distribution of primary production and sea ice proxies in surface sediments from the fjord, against monitoring data from the Greenland Ecosystem Monitoring Programme. Clear spatial gradients in organic carbon and biogenic silica contents reflected marine influence, nutrient availability and river-induced turbidity, in good agreement with in situ measurements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 44 publications
4
60
1
Order By: Relevance
“…A change in the dominant groups of palynomorphs in this region as well as the δ 13 C, δ 15 N, and C:N signature of the organic matter also points to a lower salinity. This is consistent with observations from Ribeiro et al (), Xiao et al (), and Hörner et al (), where low sedimentary IP 25 concentrations were linked to reduced salinities. IP 25 is produced in the ice and released when the sea ice melts, in contrast to HBI III, which is thought to be produced in open waters by diatoms possibly blooming near the marginal ice zone (Belt et al, ), although not exclusively (Belt et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A change in the dominant groups of palynomorphs in this region as well as the δ 13 C, δ 15 N, and C:N signature of the organic matter also points to a lower salinity. This is consistent with observations from Ribeiro et al (), Xiao et al (), and Hörner et al (), where low sedimentary IP 25 concentrations were linked to reduced salinities. IP 25 is produced in the ice and released when the sea ice melts, in contrast to HBI III, which is thought to be produced in open waters by diatoms possibly blooming near the marginal ice zone (Belt et al, ), although not exclusively (Belt et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Biogenic Silica (BSi) concentrations varied Journal of Geophysical Research: Biogeosciences 10.1002/2017JG003840 between 0.45 and 4.96 mg g À1 dry mass Si (average 1.89 mg g À1 ) ( Figure 4a and Table 3), corresponding to 0.17 to 1.06 wt % SiO 2 (average 0.40 wt % SiO 2 ). These values are low in comparison with measurements from other high-Arctic fjord regions such as the Young Sound-Tyrolerfjord, where the average value is almost 3 times higher (Ribeiro et al, 2017). This can likely be explained by a longer lasting sea ice cover in the study area, with less biogenic silica accumulating on the seafloor as the result of reduced marine productivity.…”
Section: Biogenic Silicacontrasting
confidence: 64%
See 1 more Smart Citation
“…Downcore changes in the sedimentary IP 25 concentrations from a given location are therefore typically interpreted to reflect temporal fluctuations in the sea-ice conditions. However, recent studies have shown that the sedimentary concentrations of IP 25 in coastal areas influenced by freshwater runoff are lower than expected, thus showing a mismatch with overlying sea-ice cover extent (Xiao et al, 2013;Hörner et al, 2016;Ribeiro et al, 2017;Limoges et al, 2018). Despite the growing number of IP 25 -based sea-ice reconstructions, only a limited number of studies have, to date, investigated the ecophysiological and environmental parameters that determine IP 25 production (e.g., Brown et al, 2011Brown et al, , 2014, raising concerns about the interpretation of IP 25 as a quantitative indicator of seaice cover, and the possible limitations to its application in the Arctic (Belt and Müller, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…The same consequence applies to totally ice-free conditions where no ice algae live, that is, IP 25 = 0. This difficulty in interpreting IP 25 data can be overcome by the additional use of phytoplankton-derived, open-water biomarkers such as brassicasterol and dinosterol (Müller et al, 2009(Müller et al, , 2011 or specific tri-unsaturated HBIs (Belt et al, 2015(Belt et al, , 2019Limoges et al, 2018;Ribeiro et al, 2017;Smik et al, 2016). By combining the environmental information carried by IP 25 and the different phytoplankton biomarkers (Figure 6c), even more semiquantitative estimates of present and past sea-ice coverage, seasonal variability, and marginal ice zone situations are possible (Müller et al, 2011;Belt et al, 2015Belt et al, , 2019Stein et al, 2017; for recent and critical review of this biomarker approach, see Belt, 2018).…”
Section: Proxies For Reconstructing Past Arctic Ocean Paleoenvironmenmentioning
confidence: 99%